The anthropological aspects of dentofacial deformities: A comparison between Indonesian and Dutch cohorts (Aspek antropologi kelainan bentuk dentofasial: Sebuah perbandingan antara kelompok Indonesia dan Belanda) - M. Ruslin; T. Forouzanfar; I.A. Astuti; E.S. Soemantri; D.B. Tuinzing (Journal of Dentomaxillofacial Science, 2014)
The aim of the present study was to investigate the prevalence of dentofacial deformities in an Indonesian cohortcompared with a Dutch cohort and to study the anthropological aspects of dentofacial deformities. The Indonesiancohort included 36 male and 50 female patients from Bandung. The Dutch cohort included 1,003 male and 1,623female patients from Amsterdam. The majority of the Indonesian cohort was less than 30 years old (93%)comparedwith 61.5% of the Dutch cohort. The age distribution of 31-40 years consisted of more Dutch than Indonesian patients(p<0.01). Mandibular prognathism with an open bite was the most prevalent deformity (46.5%) among the Indonesiancohort with a mean age of 22.78 (SD;6.34). Mandibular deficiency was the least prevalent deformity (2.3%) with amean age of 31 (SD;12.73). In contrast, mandibular deficiency with a normal or low mandibular plane angle was themost prevalent deformity (55.9%)among the Dutch cohort with a mean age of 30.48 (SD;1075)and mandibularprognathism with an open bite was the least prevalent deformity (3.3%) with a mean age of 22.49 (SD;6.20). Comparedto the Dutch population, the Indonesian population consisted of more mandibular prognathism (p<0.01) and lessmandibular deficiency (p<0.01). In the Indonesian cohort, young patients seek orthognathic surgery most frequently tocorrect a functional problem associated with mandibular prognathism with an open bite. It was concluded that thegreatest severity of dentofacial deformities that are observed in Southeast Asian patients.